The Natalkinskoe Gold Deposit: Formation Conditions Based on Paragenetic Analysis of Dike and Ore Vein Networks - Seminsky K.Zh.; Burzunova J.P.; Seminsky A.K.; Vursiy G.L.; Ovsov R.N.; Bortnikov N.S. (My University, 2025)
The aim of the research was to reconstruct the structural environment of ore formation for the Natalkinskoe gold deposit (NGD), which is located in the north-east of Russia and contains unique accumulations of precious metal. Based on the paragenetic analysis of fracture networks containing different types of dikes and ore veins with a known age of formation, it was established that the NGD localization is confined to the intersection of two regional fault zones. These are the longitudinal northwestern Tenka zone and the transverse sublatitudinal zone of the hidden basement fault, the kinematics of which at the stage of ore formation corresponded to left- and right-lateral strike-slip faults. It is shown that under conditions of the reconstructed strike-slip regime, the migration of mineralized solutions and ore formation were controlled by sections of the fracture network in the second-order and higher ranked extension regime. The patterns of fracture formation established for the ore stage made it possible to characterize the structural-tectonic conditions of the development of the Natalka mineral-forming system, which can subsequently be used to develop its model.
Keywords: Natalkinskoe gold deposit; orogenic gold deposits; structural geology; faults; dikes; ore veins; paragenetic analysis; stress state of rocks; stage of ore formation